GAMBARAN KARIES GIGI PADA ANAK TUNAGRAHITA DI SLB C KOTA SEMARANG - Fajar Istiqomah; Henry Setyawan Susanto; Ari Udiyono; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
A intellectual development disorder child is more comprehensively defined as individuals who have significant intelligence below average and are accompanied by the inability of the behavior adaptation, which appear in the developmental period. Dental caries and gingivitis occurs more frequently in children with special needs compared to a normal child. The prevalence of caries in Indonesia reaches 60-80% of the entire population, while one of the dental caries on mentally disabled children reaches 82,6%. This research was observational analytic with cross sectional study design. The population in this research is whole intelectual development disorder children aged 6-12 years. The cariesdata collection was obtained from the children’s DMF-T examination. Out of the 101 respondents, this study found 83,2% in caries.